“It’s Not Like I Wanted Him Kicked Off the Football Team”: Alternative Approaches to Justice and Campus Sexual Assault - Ratajczak, Kathleen (Crime & delinquency, 2024)
Current Title IX policy focuses strictly on adjudication and punishment for sexual assault on college campuses. Yet, the possibility of alternative forms of justice has long been a point of debate, with recent policy changes allowing for university choice in the application of transformative and restorative justice practices. The following study, using qualitative interviews with 23 student survivors from two universities, finds that student survivors of campus sexual assault were not focused on punishment as a remedy for their victimization. Instead, students discussed a desire to be heard, have their victimization recognized, and the creation of survivor-centered resources focused on healing and resiliency. Opportunities for alternative forms of justice that increase healing and help seeking among student survivors are discussed.